Translation in contrast to a dictionary. Theatrical and opera texts versus Polish-Russian lexicography - Parafińska-Korybska, Ewelina (Вопросы семантики и стилистики текста: лингвистический дискурс, 2021)
The main aim of the research is to examine the topicality of theatrical and operatic lexis in Polish-Russian lexicography, D. Hessen and R. Stypuła’s Wielki słownik polsko-rosyjski, Wielki słownik polsko-rosyjski edited by J. Wawrzyńczyk, and Podręczny idiomatykon polsko-rosyjski edited by W. Chlebda. The lexis to be studied was noted. The topicality degree of the dictionary resources was verified based on lexis found in the Teatr and Opera Café magazines. A large number of the units from the area of theatre and opera was noted in dictionaries. However, contemporary texts on this subject abound in numerous word combinations (often non-standard), which the dictionaries do not include. This indicates the insufficient functionality of the studied resources.